Pengembangan E-Modul dengan Model Problem Based Learning pada Mata Pelajaran PAI - Nur Aisyah; Santi Laili Safitri; Fatimatus Zahra; Dwi Irma Santoso (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2021)
Learning during the current pandemic requires innovation so that students do not miss the material. One thing that teachers can do is develop e-modules. The purpose of the e-module is so that students can continue to study independently according to their respective speeds and abilities. Research method using the Borg and Gall model with 8 systematic steps. The results of the study show that the e-module can be used properly according to expert validation and students input.